2020
DOI: 10.1142/s0217751x20410110
|View full text |Cite
|
Sign up to set email alerts
|

Searching for heavy charged Higgs bosons through top quark polarization

Abstract: We study the production of a heavy charged Higgs boson at the Large Hadron Collider (LHC) in [Formula: see text] within a 2-Higgs Doublet Model (2HDM). The chiral structure of the [Formula: see text] coupling can trigger a particular spin state of the top quark produced in the decay of a charged Higgs boson and, therefore, is sensitive to the underlying mechanism of the Electroweak Symmetry Breaking (EWSB). Taking two benchmark models (2HDM type-I and 2HDM type-Y) as an example, we show that inclusive rates, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition to the aforementioned observables, we also study the sensitivity of the following angle [21] which applies to all the spin quantization axses used here. It was also found that the energy distributions of the top quark decay products carry some information on the polarization state of the top (anti)quark [148][149][150][151][152][153][154][155][156]. We follow the same definitions used by [150,152] and study the ratios of the different energies.…”
Section: F Cp-violation Observables In the T Th 1 Channelmentioning
confidence: 99%
“…In addition to the aforementioned observables, we also study the sensitivity of the following angle [21] which applies to all the spin quantization axses used here. It was also found that the energy distributions of the top quark decay products carry some information on the polarization state of the top (anti)quark [148][149][150][151][152][153][154][155][156]. We follow the same definitions used by [150,152] and study the ratios of the different energies.…”
Section: F Cp-violation Observables In the T Th 1 Channelmentioning
confidence: 99%